2011
DOI: 10.1673/031.011.11501
|View full text |Cite
|
Sign up to set email alerts
|

DoesTribolium brevicornisCuticular Chemistry Deter Cannibalism and Predation of Pupae?

Abstract: The cuticular hydrocarbons of insects are species-specific and often function as semiochemicals. The activity of Tribolium brevicornis cuticular hydrocarbons as feeding deterrents that ostensibly function to prevent pupal cannibalism and predation was evaluated. The cuticular hydrocarbons of T. brevicornis pupae were characterized and flour disk bioassays conducted with individual and combined extract components incorporated into artificial diets on which Tribolium adults fed for six days. Feeding by T. brevic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Previous studies explored cannibalism and predation in seven Tribolium species, and examined the potential function of cuticular hydrocarbons as a chemical deterrent to cannibalism and predation behaviour (Alabi et al ., , , ). Results from our laboratory indicated Tribolium spp .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies explored cannibalism and predation in seven Tribolium species, and examined the potential function of cuticular hydrocarbons as a chemical deterrent to cannibalism and predation behaviour (Alabi et al ., , , ). Results from our laboratory indicated Tribolium spp .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most intriguing Tribolium beetle behaviours is cannibalism, and a number of studies have investigated this attribute (Alabi et al ., ; , ; Alabi, ). Cannibalism and predation are widespread among Tribolium species, and have been well described (Park et al ., , ; Stevens, ; Alabi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the ants are repelled when their antennae contact the bodies of the beetles, also suggests that other compounds that are not volatile, or not as volatile as those found in the pygidial glands of the beetles also have an effect during the attack of the ants. Alabi et al (2011) found that the cuticular compounds of Tribolium brevicornis pupae could deter predation by conspecific and congeneric beetles.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed composition and their functions have been carried out on terrestrial insects (e.g. Blomquist & Jackson, 1979;Lockey, 1980;Alabi et al, 2011;Pattanayak et al, 2014;Stiziano et al, 2015, Rajpurohit et al, 2017, whereas among aquatic ones, CHC profiles have only been described for some freshwater dytiscids (Jacob & Hanssen, 1986;Alarie et al, 1998). On the other hand, CHCs show a significant degree of plasticity conferring a notable intraspecific variability (Howard & Blomquist, 1982;Gibbs & Rajpurohit 2010).…”
Section: Introductionmentioning
confidence: 99%